THE INFLUENCE OF CUSTOMER INSPIRATION ON SOCIAL MEDIA MARKETING TOWARD ARCHITECTURAL SERVICE PURCHASE INTENTION - Sabrina Wissen; Lina Anatan (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
Social media has been used as a marketing tool by architecture firms to generate purchase intention. However, inspiration as a motivating internal response is needed to achieve the marketing objective. This study aims to examine the effect of utilitarian content, hedonic content, and openness as antecedents of customer inspiration, the effect of customer inspiration on purchase intention, and the mediating role of customer inspiration between antecedents and purchase intention. A total of 395 respondents were taken as samples using simple random sampling, and the data was then analyzed with SmartPLS. Results show that utilitarian content, hedonic content, and openness positively affect customer inspiration, and customer inspiration positively affects purchase intentions. Additionally, customer inspiration also mediates the effect of utilitarian content, hedonic content, and openness on purchase intentions. This study contributes to the literature on customer inspiration from a customer-firm relationship perspective. Moreover, this study can give insight for architectural firms to effectively practice social media marketing by focusing on creating customer inspiration through the content provided and targeting the right potential customers in order to generate architectural design service purchase intention.